Dampak Keberadaan Tengkulak Terhadap Harga Tandan Buah Segar (TBS) Sawit Dalam Perspektif Ekonomi Syariah: Studi Pada Petani Desa Lambur 1 Kabupaten Tanjung Jabung Timur - Rara Dian Setiani; Novi Mubyarto; Ferri Saputra Tanjung; Hansen Rusliani (CV. Aksara Global Akademia, 2026)
This study aims to analyze the impact of middlemen on the price of Fresh Fruit Bunches (FFB) of oil palm received by farmers in Lambur I Village, Tanjung Jabung Timur Regency, from a sharia economic perspective. This study also examines the FFB marketing patterns carried out by farmers and the factors that influence farmers in choosing where to sell their harvest. The method used is a qualitative approach with a case study research type. Data were obtained through in-depth interviews, field observations, and documentation to understand FFB marketing practices and the socio-economic relationships between farmers and middlemen. The results show that FFB marketing in Lambur I Village is carried out through three main channels: middlemen, the Marketing Chain of Trust (RAM), and palm oil processing factories. Most farmers choose to sell FFB to middlemen because the transaction process is easier, payments are fast, and transportation costs are not required. In addition, urgent financial needs, limited transportation facilities, and long-standing socio-economic relationships also influence farmers' dependence on middlemen. In practice, middlemen play a dominant role in determining prices, deducting approximately Rp 250–Rp 300 per kilogram from the factory price. From a sharia economic perspective, marketing practices through middlemen are essentially permissible as long as they are carried out with mutual consent and do not contain elements of usury, gharar, or injustice. However, the dominance of middlemen in determining prices indicates a bargaining imbalance that could potentially harm farmers, thus not fully reflecting the principle of justice in sharia economics